Effect of high-dose fentanyl on renal function in dogs - Castiglia, Yara Marcondes Machado; Braz, José Reinaldo Cerqueira; Vianna, Pedro Thadeu Galvão; Lemonica, Lino; Vane, Luiz Antonio (São Paulo Medical Journal, 1997)
Our objective was to determine the effects of high-dose fentanyl on canine renal function (RF). We anesthetized with sodium pentobarbital (SP) 16 dogs, randomly divided into 2 groups: in G1, SP was given alone, and in G2, combined with 0.05 mg.kg-1 fentanyl. All animals were ventilated artificially and had catheterized left and right femoral veins and left femoral artery for fluid infusion, drug administration, blood collection, and hemodynamic measurement. Urine was collected throughout the experiment. Attributes of RF were studied. SP did not alter RF, which was significantly altered by fentanyl. In G2, slower heart rates, mean arterial pressure, creatinine clearance, urinary output, osmolar clearance and fractional excretion of sodium and potassium were observed. G1 had a behavior attributed to extracellular volume expansion and no RF alterations. In G2, we observed significant decreases in RF due to opioid-induced hemodynamic changes, not discarding the possible action of aldosterone.